2002
DOI: 10.2144/02333dd04_11831a
|View full text |Cite
|
Sign up to set email alerts
|

Production of Antigen-Specific Human Monoclonal Antibodies: Comparison of Mice Carrying IgH/κ or IgH/κ/λ Transloci

Abstract: Here we compare human monoclonal antibody (MAb) production from mouse strains that carry disruptions of their endogenous mouse IgH/Igκ loci and harbor human IgM + Igκ (BABκ) or human IgM + Igκ + Igλ transloci (BABκ,λ). We found that whereas both strains proved effective for the isolation of antigen-specific IgM antibodies, many of the IgM MAbs elicited from BABκ comprise human µ chains that are associated with mouse λ chains. In contrast, BABκ,λ mice gave rise to fully functional, polymeric human IgM antibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Of the two mAb derived from the LMB1 mice, one was fully human whereas the other consisted of a human heavy chain and a mouse light chain. Expression of mouse Ig light chains has been previously detected in hybridoma clones from transgenic humanized mice [18]. The mAb170 derived from five-feature mice strongly recognized the intact AChR and was capable of modulating the AChR in CN21 cell cultures, suggesting that it is directed against a pathogenic epitope.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Of the two mAb derived from the LMB1 mice, one was fully human whereas the other consisted of a human heavy chain and a mouse light chain. Expression of mouse Ig light chains has been previously detected in hybridoma clones from transgenic humanized mice [18]. The mAb170 derived from five-feature mice strongly recognized the intact AChR and was capable of modulating the AChR in CN21 cell cultures, suggesting that it is directed against a pathogenic epitope.…”
Section: Discussionmentioning
confidence: 96%
“…mAb170 and mAb11.14 were found to have a human k chain and mAb5.2 has a human j chain, whereas mAb40.16 has a murine k chain (data not shown). The murine k isotype of the later mAb can be explained by the fact that the endogenous Igk locus was not disrupted; a number of antibodies having mouse k chains have been produced from these mice [18]. In conclusion, three fully human mAb specific for the native human AChR were produced from these transgenic mice.…”
Section: Production Of Human Anti-achr Mab In Transgenic Micementioning
confidence: 93%
“…Despite this and the lack of class switching from IgM to IgG in these mice, the IgM response underwent efficient affinity maturation as demonstrated by the derivation of the high-affinity MAbs N3C5 and N03B11. Prior studies using human Ig-producing transgenic mice have demonstrated their suitability for deriving MAbs against antigens such as human blood cells, tumor cell lines, haptens, the human acetylcholine receptor, and HIV-1 Env antigens (20,21,28,38,55). Interestingly, the immunization of the XMG2 XenoMouse strain with gp120 SF162 allowed the isolation of IgG2() MAbs that displayed neutralizing activity against the autologous primary isolate HIV-1 SF162 , FIG.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of human Ig loci in these mice was carried out using various vectors, such as miniloci, yeast and human artificial chromosomes (YACs and HACS, respectively) and P1 vectors. Transgenic mice can be immunized with almost any Ag (including human tumor cells), and their spleens can be used to obtain hybridomas following the conventional protocol [46][47][48][49]. Moreover, mice can produce human Abs of intermediate/high affinity because they can introduce mutations in their human Igs transgenes through the mechanism of somatic hypermutation.…”
Section: Figurementioning
confidence: 99%